Molecular Epidemiology of G6PD Genotypes in Different Ethnic Groups Residing in Saharan and Sahelian Zones of Mauritania - Oum Kelthoum Mamadou Djigo; Mohamed Salem Ould Ahmedou Salem; Sileye Mamadou Diallo; Mohamed Abdallahi Bollahi; Boushab Mohamed Boushab; Aymeric Garre; Nasserdine Papa Mze; Leonardo Basco; Sébastien Briolant; Ali Ould Mohamed Salem Boukhary (Pathogens, 2021)
Plasmodium vivax malaria is endemic in Mauritania. Individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency may develop acute hemolytic anemia when exposed to 8-aminoquinoline antimalarial drugs, which are indispensable for a complete cure. The prevalence of G6PD allelic variants was assessed in different ethno-linguistic groups present in Mauritania. A total of 996 blood samples (447 males and 549 females; 499 white Moors and 497 individuals of black African ancestry) were collected from febrile patients in 6 different study sites: Aleg, Atar, Kiffa, Kobeni, Nouakchott, and Rosso. The presence of the African-type G6PD A- (G202A, A376G, A542T, G680T, and T968C mutations) and the Mediterranean-type G6PD B- (C563T) variants was assessed by PCR followed by restriction fragment length polymorphism and/or DNA sequencing. The prevalence of African-type G6PD A- genotype was 3.6% (36/996), with 6.3% (28/447) of hemizygote (A-) males and 1.5% (8/549) of homozygous (A-A-) females. Forty of 549 (7.3%) women were heterozygous (AA-). The following genotypes were observed among hemizygous men and/or homozygous women: A376G/G202A (22/996; 2.2%), A376G/T968C Betica-Selma (12/996; 1.2%), and A376G/A542T Santamaria (2/996; 0.2%). The Mediterranean-type G6PD B- genotype was not observed. The prevalence rates of G6PD A- genotype in male (10/243; 4.1%) and heterozygous female (6/256; 2.3%) white Moors were lower (p < 0.05) than those of males (18/204; 8.8%) and heterozygous females (34/293; 11.6%) of black African ancestry. There were only a few homozygous women among both white Moors (3/256; 1.2%) and those of black African ancestry (5/293; 1.7%). The prevalence of G6PD deficiency in Mauritania was comparable to that of neighboring countries in the Maghreb. Because of the purportedly close ethnic ties between the Mauritanian white Moors and the peoples in the Maghreb, further investigations on the possible existence of the Mediterranean-type allele are required. Moreover, a surveillance system of G6PD phenotype and/or genotype screening is warranted to establish and monitor a population-based prevalence of G6PD deficiency.